Does Comorbid Depression Predict Subsequent Adverse Life Events in Youth with Attention-Deficit/Hyperactivity Disorders? - Daviss, W. Burleson (Mary Ann Liebert, Inc., 2012)
OBJECTIVES: Studies have primarily focused on adverse life events (ALEs) as potential causes rather than as outcomes of pediatric depression. The current study prospectively examines ALEs in a sample of youth with attention-deficit/hyperactivity disorders (ADHD) to determine whether having a major depressive disorder (MDD) at baseline (T1) predicts counts of child-dependent or child-independent ALEs at a second assessment (T2) ∼8 months later. METHODS: Subjects with ADHD 11–18 years old were drawn mostly from a tertiary mental health clinic and evaluated with semi-structured diagnostic interviews, and parent and teacher questionnaires of ADHD severity. Eighteen with and 61 without initial MDD at T1 were compared at T2 regarding counts of subsequent overall, child-dependent, and child-independent ALEs reported on life events questionnaires by the child or parent. RESULTS: The group initially with MDD had higher overall ALEs (p=0.01) and child-dependent ALEs (p≤0.001) but not child-independent ALEs (p=0.12) at T2 relative to the nondepressed group, although only 3 of 18 continued to meet full criteria for MDD. The group initially with MDD also had a higher baseline ADHD severity (p=0.04) and proportion of oppositional or conduct disorders (p=0.004). In multivariate analyses, the group initially having MDD had a higher adjusted mean at T2 of child-dependent ALEs (p=0.02), but not of overall ALEs (p=0.06), after controlling for other T1 variables, including ALEs of the same type, ADHD severity, externalizing disorders, and the interaction of externalizing disorders with MDD. CONCLUSIONS: These findings suggest that child-dependent ALEs are potentially an important outcome after youth with ADHD have an episode of MDD. Youth with ADHD who develop comorbid MDD should be closely monitored and offered interventions to address the potential burden of child-dependent ALEs lingering after a depressive episode.